ChemInform Abstract: Diastereoselective Metal‐Catalyzed Synthesis of C‐Aryl and C‐Vinyl Glycosides. Issue 11 (8th March 2013) - Nicolas, Lionel; Angibaud, Patrick; Stansfield, Ian; Bonnet, Pascal; Meerpoel, Lieven; Reymond, Sebastien; Cossy, Janine
Abstract Cobalt‐catalyzed cross‐coupling of aryl and vinyl Grignard reagents with mannose (I) and galactose (X) is highly diastereoselective to give only the α‐products.